Modal analysis of car disc brake - Ahmad Zaki, Che Zainol Ariff (2010)
This thesis deals experiences on finding natural frequency and the mode shape of disc brake. The test is done in both simulation and also experimental using a simple test rig. The disc brake is modeled using commercial computer aided design (CAD) software, Solidworks and simulation analysis is done using commercial computational aided engineering (CAE) software, ALGOR. Experimental is done by using impact hammer to excite the disc brake and data recorded using data acquisition system (DAS) connected to sensor located on the disc brake. The results for both simulation and experimental is compared. The mode shapes is simulated using ALGOR. The differences in the results between simulation and experimental is discussed. The final selected natural frequency for simulation is based on mesh aspect ratio of 60%. Simulation natural frequency in 1st mode is 915.07 Hz, 2nd mode is 1584.63 Hz, 3rd mode is 1810.05 Hz, 4th mode is 2225.86 Hz, 5th mode is 2510.06 Hz and 6th mode is 2834.96 Hz . Meanwhile, the experimental natural frequency in 1st mode is 912 Hz, 2nd mode is 1600 Hz, 3rd mode is 1798 Hz, 4th mode is 2234 Hz, 5th mode is 2480 Hz and 6th mode is 2796 Hz . The discrepancy errors recorded between simulation and experimental is ranging from -0.961 to 0.670 %. Both mode shape of the natural frequency are discussed and analyzed.